UJI AKTIVITAS ANTIBAKTERI SEDIAAN OBAT KUMUR EKSTRAK ETANOL DAUN MANGGA HARUMANIS (MANGIFERA INDICA, L) TERHADAP STREPTOCOCCUS MUTANS PENYEBAB KARIES GIGI - Nurdianti, Lusi (Journal of Pharmacopolium, 2020)
Dental caires is a disease of the oral cavity caused by the bacterium Streptococcus mutants. Treatment is usually done by using mouthwash which if used continuously will cause side effects. Therefore, need to develop mouthwash preparations from natural ingredients. One of the potential plants is mango harumnais (Mangifera Indica, L) leaves which contain flavonoids, saponins, tannins and polyphenols as antibacterial. This study aims to determine the activity of the ethanol extract of haruman mango leaves mouthwash that can affect the growth of streptococcus mutants? bacteria and produce stable preparations during the storage period. By varying the concentration of harumanis mango leaf extracts of 10, 15, and 20%, the concentration was based on the MIC results of the ethanol extract of harumanis mango leaf. The results of testing preparations that have the potential as an antibacterial are in formula III with the formation of the largest inhibitory zone of 5.35 mm, formula II 5.06 mm, formula III 3.26 mm. The mouthwash of ethanol extract of harumanis mango leaves (Mangifera Indica, L) meets the requirements and the preparation is stable in a 30-day storage period.